Réponses

Meilleure réponse !
2014-03-20T09:26:10+01:00
Bonjour

a: (x + 1)(x + 12) = 0
x + 1 = 0   ou  x + 12 = 0
x = -1   ou   x = -12

b: (10y + 16)(-y - 3) = 0
10y + 16 = 0   ou  -y - 3 = 0
10y = -16   ou   -y = 3
y = -16/10   ou  y = -3
y = -1,6   ou  y = -3

c:(x + 13)(-1 - 3x) = 0
x + 13 = 0   ou  -1 - 3x = 0
x = -13   ou  -3x = 1
x = -13 ou  x = -1/3

d: (a + 11)(-7 + a) = 0
a + 11 = 0   ou  -7 + a = 0
a = -11  ou  a = 7

e: (5b - 15)(-b + 33) = 0
5b - 15 = 0   ou  -b + 33 = 0
5b = 15   ou   -b = -33
b = 15/5   ou   b = 33
b = 3   ou  b = 33

f: (-16 + y)(-7y - 8) = 0
-16 + y = 0   ou  -7y - 8 = 0
y = 16   ou  -7y = 8
y = 16   ou  y = -8/7